IMPLEMENTASI FACE RECOGNITION, SENSOR GETAR DAN PASSWORD SEBAGAI PENGAMAN GANDA PADA SMART DOOR LOCK BERBASIS IOT : Teknik Elektro - Nurhafidzah; Nawawi, Muhammad; Al Rasyid, Johansyah (JURNAL TELISKA, 2023)
The development of door lock technology is now sophisticated with the existence of various smart door lock innovations using sensors, cards, fingerprints, passwords, to face recognition or voice recognition. This is because the conventional keys on the market have an inadequate level of security, such as being easily lost and duplicable. This research aims to implement a double security system at the door with an innovative idea that combines face recognition, vibration sensors, and passwords which of course has better security than locks or locks. Identification technology that will be used in face recognition uses a Histogram of Oriented Gradients (HOG). The system created is based on the Internet of Things (IoT) which can provide information and early warning through notifications in the form of photos and messages that an unknown person has been detected in front of the house on a telegram in real time.